IMPLEMENTASI KEGIATAN BERCERITA DALAM CIRCLE TIME UNTUK MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA DINI DI RA MUSLIMAT AL UTSMANI GEJLIG KAJEN - lutfiyanah; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Language development in early childhood constitutes one of the most fundamental aspects of child development, as it serves as the primary medium for self-expression and social interaction. This study aims to describe the implementation of storytelling activities during circle time and to analyze their contribution to the language development of early childhood at RA Muslimat Al Utsmani Gejlig Kajen. This research employed a descriptive qualitative approach. Data were gathered through participatory observation, in-depth interviews, and documentation. The validity of data was ensured through source and technique triangulation. The subjects consisted of 15 children aged 4–5 years. The results show that storytelling activities conducted within the circle time framework effectively enhanced children's language competencies, particularly in the domains of listening comprehension and oral expression. Approximately 66% of children demonstrated the ability to follow the story's narrative, respond to the teacher's questions, and retell stories using their own words. Meanwhile, 20% required additional prompting, and 14% still experienced challenges in maintaining concentration and speaking confidently. These findings affirm that interactive storytelling within a circle time setting creates a conducive and enjoyable learning environment that stimulates children's active participation and enriches vocabulary. It is recommended that future research employ experimental or quasi-experimental designs to further validate the effectiveness of this approach.